PERANCANGAN DAN IMPLEMENTASI APLIKASI M-COMMERCE DENGAN KONSEP BUSINESS TO COSTUMER (B2C) BERBASIS ANDROID PADA TOKO CALISTA COLLECTION GUNUNG PANGILUN PADANG - Ridho Perwira Niza; Silfia Andini; erlinda erlinda (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
M-Commerce with the Business To Costumer (B2C) concept is an application that is used by the Calista Collection Store as a means to support technological progress, especially in the field of fashion sales, especially in the field of women's fashion. The Calista Collection store records and processes data, processes the quantity and price of goods, and sells it manually, using a ledger, because there is no computerized system. Calista Collection store wants to expand its marketing throughout the city of Padang and outside the city of Padang by utilizing internet technology in this case the M-Commerce application is a means to support the progress in selling Fashion. This M-Commerce application sales of goods can be seen through categories and can also be through home. Sales using the M-Commerce application with the concept of Android-based Busines To Costumer (B2C) can make it easier for leaders / managers of Calista Collection to promote their fashion and also increase profits. sales while expanding its marketing area.